Effects of anthropogenic sounds on the behavior and physiology of the Eastern oyster (Crassostrea virginica) - Ledoux, Tamara; Clements, Jeff C.; Comeau, Luc A.; Cervello, Gauthier; Tremblay, Réjean; Olivier, Frédéric; Chauvaud, Laurent; Bernier, Renée Y.; Lamarre, Simon G. (Frontiers in Marine Science, 2023)
Noise pollution is a major stressor in the marine environment; however, responses of economically and ecologically important invertebrates, such as oysters, are largely unknown. Under laboratory conditions, we measured acute behavioural and physiological responses of eastern oysters (Crassostrea virginica) to sound treatments mimicking human activity in the environment. Oysters immediately reduced their valve gape under simulated pile driving sound, but not drilling or boating sound. Pile-driving sound also reduced adductor muscle glycogen, but not triglyceride. None of the sound treatments affected longer-term (12 hours) valve activity levels after the administration of sounds. Interestingly, neither acute nor longer-term valve gaping responses were correlated with glycogen content on the individual level, suggesting that the observed behavioural responses to sound were not mechanistically driven by energetic physiology. Our results suggest that C. virginica responds to some, but not all, anthropogenic sounds. Future studies assessing downstream effects on growth, reproduction, and survival in the wild are needed to better understand the effects of anthropogenic sounds on oyster populations and the biological communities they support.